Layer-by-layer assembly of NaYF4:Yb3+/Er3+ UCNPs@Cystein and UCNPs@Cys-Ab as hybrid bio-optical sensors for E. coli bacteria - Ramin, Beatriz B.S. [UNESP] (2024)
An innovative bio-optical Layer-by-Layer sensor was developed for the detection of Escherichia coli (E. coli) bacteria. This groundbreaking sensor utilizes upconversion NaYF4:Yb3+/Er3+ nanoparticles (UCNPs) that have been modified with cysteine (UCNPs@Cys) and E. coli antibodies (UCNPs@Cys-Ab). The optical sensing system employed Layer-by-Layer (LbL) films of UCNPs, harnessing the emission of rare earth nanoparticles to detect the presence or absence of E. coli. The incorporation of Ab into the UCNPs@Cys nanoparticle was confirmed through SEM-EDS imaging, resulting in the formation of aggregated UCNPs@Cys-Ab microparticles with an approximate diameter of 2 μm. To further analyze the sensing capability, Principal Component Analysis (PCA) was employed to examine the differences between the UCNPs@Cys and UCNPs@Cys-Ab sensors. The results indicated that the incorporation of antibodies to the optical system significantly enhanced sensor sensitivity. This improvement was evident in the expanded detection range, which spanned from 2 × 103–106 CFU/mL, and the remarkably low limit of detection (LOD) value of 34 CFU/mL. These findings highlight the extensive potential of the UCNPs@Cys-Ab as a sensor. Furthermore, it was demonstrated the sensor's enhanced sensitivity and broad detection range make it an invaluable tool for ensuring the well-being of communities by enabling effective management of potential E. coli contamination.